2016
DOI: 10.1302/0301-620x.98b3.36775
|View full text |Cite
|
Sign up to set email alerts
|

The impact of patient and surgical factors on the rate of infection after primary total knee arthroplasty

Abstract: Infection rates in TKA are related to both individual patient and surgical factors, and some modern methods of reducing infection may actually increase infection risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(70 citation statements)
references
References 33 publications
5
64
0
1
Order By: Relevance
“…As a result of the relatively small number of THAs with ASA and BMI recording with followup longer than 6 months, we elected to exclude these two PJI risk parameters from the multivariate risk analysis. This is potentially important, because in some studies, the effect size of the increased risk of infection associated with higher BMIs and ASA classes [10,15] is comparable to the effect size we observed here in association with bearing surfaces. This suggests that some or all of the observed effect associated with bearing surface could have been the influence of those potentially confounding variables.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…As a result of the relatively small number of THAs with ASA and BMI recording with followup longer than 6 months, we elected to exclude these two PJI risk parameters from the multivariate risk analysis. This is potentially important, because in some studies, the effect size of the increased risk of infection associated with higher BMIs and ASA classes [10,15] is comparable to the effect size we observed here in association with bearing surfaces. This suggests that some or all of the observed effect associated with bearing surface could have been the influence of those potentially confounding variables.…”
Section: Discussionsupporting
confidence: 82%
“…Because of this rather homogeneous practice, we elected to exclude the factor preoperative antibiotic prophylaxis from multivariate analysis. Also, operative time was not used for analysis; a recent Registry study showed no association with the risk of revision for PJI in TKA [15].…”
Section: Methodsmentioning
confidence: 99%
“…Their multivariate analysis showed that using surgical helmet system has a trend towards significance for deep infection. They concluded that there is no evidence in favor of modern surgical helmet system decreasing PJI, they may even increase the risk of infection in primary TKR (14).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, recent data from the New Zealand Joint Registry and the Kaiser Joint Registry show similar findings. 5,6 This observation has previously attracted little attention. It can serve as fertile area for the generation and testing of hypotheses with more detailed research, and will hopefully lead to interventions that reduce the risk.…”
Section: Observationmentioning
confidence: 99%